Reexamination of Okun’s law: Empirical analysis from Panel Granger Causality - Sasongko, Gatot; Artanti, Niken Putri; Andrian; Lee , Cheng-Wen (Industrija, 2020)
Unemployment has been such a problem and a significant focus in several countries, especially in developing countries such as Indonesia. In its journey, the economic development process causes various impacts, such as economic structure, institutions, and community life patterns. This study aims to confirm the existence of Okun’s coefficients in Indonesia. We conduct panel data of 34 provinces in Indonesia from 2014 to 2019, obtained from the Central Bureau of Statistics. The data was analyzed using the panel data model and Panel Granger Causality (an alternative to capture possible variations between economic growth and open unemployment). The Panel Granger causality analysis results show that there was one-way causality between economic growth and unemployment. It pictured several influencing factors, such as education level (an essential qualification needed in the labor market) which made it difficult for those who did not attend higher education to get a job and were vulnerable to being unemployed. Similarly, the labor force also continued to increase along with the increasing population and employment opportunities that should have absorbed labor.